2014
DOI: 10.1007/s10549-014-2960-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of menopausal hormone therapy and risk of ductal and lobular breast cancer among women 55–74 years of age

Abstract: Background The Women’s Health Initiative (WHI) randomized trials found that use of combined estrogen and progestin menopausal hormone therapy (CHT) increases breast cancer risk, but use of unopposed estrogen hormone therapy (EHT) does not. However, several questions regarding the impact of hormone use on risk of different types of breast cancer and what thresholds of use confer elevations in risk remain. Methods We conducted a population-based case-control study among women 55–74 years of age to assess the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Compared to IDC tumors, ILC tumors are more commonly ER+ [20] which offers a potential mechanism for the stronger association with ILC cancers. This is further supported by evidence from previous studies showing an association between postmenopausal hormone therapy and risk of ILC [21, 22]. …”
Section: Discussionsupporting
confidence: 85%
“…Compared to IDC tumors, ILC tumors are more commonly ER+ [20] which offers a potential mechanism for the stronger association with ILC cancers. This is further supported by evidence from previous studies showing an association between postmenopausal hormone therapy and risk of ILC [21, 22]. …”
Section: Discussionsupporting
confidence: 85%
“…As already published by several authors , we observe that the risk of the second most common type of breast cancer, invasive lobular carcinoma is more strongly associated with HT use than the risk of other nonlobular invasive subtypes; HR = 3.10 (2.51–3.81) versus 1.94 (1.78–2.12). For DCIS, published data have varied.…”
Section: Discussionsupporting
confidence: 73%
“…The decline in LCIS incidence among women ages 50 to 69 years is notable, because studies have shown stronger associations between MHT use and ILC than between MHT use and IDC. 82 Treatment Patterns for DCIS and LCIS Figure 3 illustrates surgical treatment patterns for women who were diagnosed with a first primary DCIS or LCIS in the United States from 2007 to 2011. Among women of all ages who were treated for DCIS, BCS was the most common surgical treatment (69%), followed by unilateral mastectomy (19%), bilateral mastectomy (8%), and no surgery (4%).…”
Section: Breast Carcinoma In Situ Incidence Trendsmentioning
confidence: 99%